농업·농촌종합대책 투융자사업 평가모형의 정립 및 향후 투융자계획 조정방안 연구 - 김용택 (한국농촌경제연구원, 2006)
This study attempts to evaluate the performance of the 119 Trillion Comprehensive Plans for the agricultural and rural development and to provide the basic data which helps determine the future direction of the agricultural public finance policy to actively respond to the rapidly changing environments surrounding the Korean agriculture. One of important factors resulting from the implementation of the expanded agricultural public funds over 10 years is the efficient usage of the public funds as well as the expansion of the public funds to offset income losses of farmers from the openness of agricultural markets. The studies and researches in relation to the performance of the agricultural public finance focussed mainly on the performance of agricultural development projects. This study, however, focuses on the inter-relationship between agriculture and the national economy. In other words, this study investigates the effects of the agricultural public finance on both agriculture and the rest of economy. The important implication of this study is the importance of the expanded public funds to agriculture as well as the whole economy. In order to derive the people consensus, it is necessary to show the effects of the expansion of public funds on the agriculture sector and rural area objectively.